Preferential carriage of class 2 integrons in Acinetobacter baumannii CC113 and novel singletons. - Ramirez, Maria Soledad (2015)
Our understanding of the distribution of integrons associated with multidrug resistance in Acinetobacter baumannii isolates around the world remains incomplete. The association between the class 1 and 2 integron A. baumannii-positive isolates (n = 60), recovered since 1982 from 11 Argentinean hospitals, and the circulating lineages, was investigated. While class 2 integrons were highly significantly associated with clonal lineage CC113B/CC79P (P = 0·009) and novel singletons (P = 0·001), class 1 integrons were found not to be associated with CC109B/CC1P or other lineages. The study reveals a differential distribution of class 2 integrons in lineages, and suggests that the prevalence of intI2 in Argentina is related to the emergence of novel singletons in recent years and to the abundance of CC113B/CC79P, which has been the local dominant lineage for several decades.